Quality of visual fields, GIS and residents´ perception in social housing - Reis, Antonio Tarcisio da Luz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper investigates the aesthetic quality of views from the living-room of housing units, for low income people. It is explored how universal the findings for other urban contexts are, including the importance of views and their elements for low income housing, and how the residents feel about the views from the living-rooms of their housing units. Using GIS (Geographical Information System) a more effective analytical method for describing elements or characteristics of views is developed, including distances between view elements and the observer. In 12 housing estates in the metropolitan region of Porto Alegre, data were collected by means of qualitative and quantitative methods, such as interviews, physical measurements, and questionnaires applied to a total sample of 374 housing units. Analysis of the data included the use of non-parametric statistical tests, such as Kruskal-Wallis and Spearman rank correlation, apart from the analysis using GIS. The results revealed, for example, that the effect provoked by the different element types included in the views is similar to those already found in other contexts. The analytical method developed using GIS indicates that from a certain distance the visual barriers do not interfere in the aesthetic quality of views.